Comparison of the Impacts of a Dynamic Exercise Program vs. a Mediterranean Diet on Serum Cytokine Concentrations in Women With Rheumatoid Arthritis. A Secondary Analysis of a Randomized Clinical Trial - Lozada-Mellado, Mariel; Llorente, Luis; Hinojosa-Azaola, Andrea; García-Morales, José M.; Ogata-Medel, Midori; Alcocer-Varela, Jorge; Pineda-Juárez, Juan A.; Castillo-Martínez, Lilia (Frontiers in Nutrition, 2022)
Background: Rheumatoid arthritis (RA) is a disease characterized by a chronic inflammatory state. High pro-inflammatory cytokine levels are associated with disease activity. Exercise and the Mediterranean diet (MD) exert anti-inflammatory effects; however, their impacts on inflammation in RA patients remains unknown. This study aimed to compare the effects of six-months of dynamic exercise program (DEP) vs. MD on pro- and anti-inflammatory cytokine serum concentrations. Methods: Secondary analysis of a randomized clinical trial in which 90 women with RA were randomly assigned to the DEP (n=30), MD (n=30), or control group (n=30). All patients received pharmacological treatment. Serum concentrations of pro-inflammatory (TNF-α, TNF-β, IL-1β, IL-6 pg/mL) and anti-inflammatory (IL-10, IL-Ra pg/mL) cytokines were measured at baseline and after six months using the Luminex technique. Results: After six months of follow-up, we found an improvement of the median percentages changes concentrations of TNF-α (DEP, -12.3; MD, -13.3; control, 73.2; p=0.01), TNF-β (DEP, -67.4; MD, -54.9; control, 0; p=0.04), and IL-6 (DEP, -19.9; MD, -37.7; control, 45.5; p=0.04) in the DEP and MED groups in comparison with control group. IL-1Ra concentrations increased only in the MD group (13.8) compared to levels in the control group (-31.7), p=0.04. There were no statistically significant differences between DEP and MD groups. Only n=27 participants in the DEP group, n=26 in the MD group, and n=21 in the control group completed the follow-up. Conclusion: The DEP and the MD have potential effects in the concentrations of pro-inflammatory cytokines compared with those in a control group. Only the MD elevated the concentration of IL-Ra. Registered under ClinicalTrials.gov identifier no. NCT02900898